It’s Look, That’s Go: Usage-Based Innovation in Asian Englishes - Zayani Zainal Abidin (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2026)
This study extends previous research on the it’s + Vø pattern in Asian English as a lingua franca (ELF) by presenting the first comparative analysis of the it’s + Vø (e.g., it’s look for ‘it looks’) and that’s + Vø constructions (e.g., that’s go for ‘that goes’). It examines how usage frequency, functional motivations, and cognitive mechanisms shape constructional innovation across three English domains: institutionalised varieties, ELF interactions, and learner Englishes. Using a mixed-method approach that combines frequency and distributional analysis, collocational and collostructional profiling, and qualitative discourse analysis, the study systematically compares the constructions to identify structural and contextual motivations underlying their use. Findings show that it’s + Vø is more frequent, lexically diverse, and socially widespread than that’s + Vø, with highest productivity in learner Englishes, moderate entrenchment in ELF use, and marginal presence in institutionalised varieties. Analysis of recurring bare-verb patterns and functional clustering indicates fluid and context-responsive usage in ELF interactions, whereas learners’ preference for evaluative or stance-marking expressions reflects pragmatic overextension. These patterns suggest ongoing processes of diffusion, schematic extension, and functional adaptation rather than stable conventionalisation. The study contributes to usage-based accounts of grammatical innovation in Asian Englishes and reframes these constructions as functionally motivated rather than erroneous.